1968
DOI: 10.1149/1.2410864
|View full text |Cite
|
Sign up to set email alerts
|

The Nickel∕Nickel Fluoride Anode in Wet Hydrogen Fluoride

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although previous experiments have suggested the formation of active nickel fluorides such as NiF 3 or NiF 4 on the Ni anode, compelling physical evidence is still missing. Additionally, the electrochemical polarization and passivation behavior of nickel in various electrolytes such as (anhydrous) HF, organic substrates dissolved in HF, and HF‐containing electrolytes such as NEt 3 ⋅ 3 HF have been intensively investigated in the past . However, a detailed understanding of the ECF process is still missing and the active species in a Simons‐type ECF has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous experiments have suggested the formation of active nickel fluorides such as NiF 3 or NiF 4 on the Ni anode, compelling physical evidence is still missing. Additionally, the electrochemical polarization and passivation behavior of nickel in various electrolytes such as (anhydrous) HF, organic substrates dissolved in HF, and HF‐containing electrolytes such as NEt 3 ⋅ 3 HF have been intensively investigated in the past . However, a detailed understanding of the ECF process is still missing and the active species in a Simons‐type ECF has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…ESCA studies under these conditions have confirmed the presence of a thin oxide layer between the Ni substrate and the NiF 2 film [52]. When the H 2 O content exceeds 2%, anodic polarisation in AHF leads to the formation of OF 2 [47].…”
Section: Liquid Hf Mediummentioning
confidence: 72%
“…The electrocatalytic properties of Ni towards F 2 generation and electrochemical fluorination were also found to improve in the presence of trace levels of water [45,47]. ESCA studies under these conditions have confirmed the presence of a thin oxide layer between the Ni substrate and the NiF 2 film [52].…”
Section: Liquid Hf Mediummentioning
confidence: 76%
See 2 more Smart Citations